Peculiarities of Movement Plastique Development in Young Gymnasts - T. Kravchuk; N. Sanzharova; A. Udovika (OVS LLC, 2018)
The purpose of this study was to substantiate and create a technique for the development of movement plastique in gymnastics at the initial training stage and experimentally verify its effectiveness. Materials and methods: The study participants were 28 boys aged 6-7 engaged in gymnastics (14 - control group and 14 - experimental group). To achieve the purpose set, the study used the following research methods: analysis of scientific and methodological literature, pedagogical testing and methods of mathematical statistics. Results: The use of a special technique that includes exercises developing expressive movements, exercises of classical and parterre choreography, rhythmic gymnastics and elementary dance exercises at the initial training stage in gymnastics improved the development level of movement plastique and its individual components, in particular the amplitude and dynamism (at p<0.05), the accuracy and the degree of using accompanying movements (at p<0.001). The study revealed strong and average correlations between the individual indicators and movement plastique in general. Conclusion: The study defined the criteria and modern requirements for gymnasts' movement plastique, as well as its individual indicators: amplitude, accuracy, degree of using accompanying movements, and dynamism. The study created a technique for the development of movement plastique in young gymnasts and experimentally proved its effectiveness.